2016
DOI: 10.5301/jabfm.5000318
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Annealing on the Structure and Magnetic Properties of Fe80B20 Magnetostrictive Fibers

Abstract: In this study, Fe80B20 amorphous fibers with the diameter of 60 μm were prepared by the single roller melt-spinning method and annealed at 200°C, 300°C, 400°C, and 500°C, respectively. XRD results indicate that the fiber structure remains amorphous when the annealing temperature is below 400°C. α-Fe phase and Fe3B phase appear when the annealing temperature rises to 500°C, which is above the crystallization temperature of 449°C. The recrystallization activation energy is calculated to be 221 kJ/mol. The coerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…In [10], it was determined that Ni in the composition has a strong in- fluence on the magnetic properties and is the main factor to get soft magnetic properties, by creating an anisotropy field and reducing the coercive force. The authors of [11] found that processing of amorphous Fe 80 B 20 alloy at 449 ∘ C worsens the soft magnetic properties and leads to an increase in the coercive force. As can be seen from numerous studies, the choice of a chemical composition and a processing mode is the main factor to obtain various required magnetic parameters depending on the purpose.…”
Section: Introductionmentioning
confidence: 99%
“…In [10], it was determined that Ni in the composition has a strong in- fluence on the magnetic properties and is the main factor to get soft magnetic properties, by creating an anisotropy field and reducing the coercive force. The authors of [11] found that processing of amorphous Fe 80 B 20 alloy at 449 ∘ C worsens the soft magnetic properties and leads to an increase in the coercive force. As can be seen from numerous studies, the choice of a chemical composition and a processing mode is the main factor to obtain various required magnetic parameters depending on the purpose.…”
Section: Introductionmentioning
confidence: 99%